Clinical Performance of Nano-Coated Orthodontic Materials In Vivo: A Systematic Review - Maria Arampatzi; Theodora Fanaropoulou; Moschos A. Papadopoulos (Applied Sciences, 2026)
Background: Nanotechnology-based surface coatings show promise in enhancing the antibacterial activity and mechanical performance of orthodontic materials. Although numerous in vitro studies suggest some benefits, the clinical relevance of these effects in vivo remains uncertain. Objectives: The aim of this systematic review was to assess whether nanocoated orthodontic materials improve clinical and clinically derived laboratory outcomes in in vivo human studies, including microbial adhesion, enamel mineralization, surface characteristics and other treatment-related parameters. Materials and Methods: An electronic literature search was conducted up to 31 July 2025, yielding 15,330 records after duplicate removal. Only in vivo studies using nanocoated materials in patients undergoing orthodontic treatment were included. Study selection, data extraction, risk-of-bias assessment and certainty-of-evidence assessment were performed independently by two reviewers. Risk of bias was assessed using RoB 2 and ROBINS-I, and certainty of evidence was evaluated using GRADE. Results: A total of 13 studies were included in the qualitative synthesis. The comparative appliances were coated and uncoated brackets, tubes, archwires, miniscrews and modules. Most studies primarily assessed microbial outcomes. Overall, nanocoated orthodontic appliances showed promising antimicrobial properties and lower bacterial adhesion in several studies. Other studies assessed enamel demineralization, surface characteristics, bond failure, orthodontic miniscrew success rate and rate of canine retraction. Conclusions: Although the included studies indicate promising results, confidence is limited by heterogeneity in nanoparticle types, coating protocols and outcome measures. Safety outcomes, including coating degradation and long-term local or systemic effects, were not adequately assessed. Further well-designed randomized trials with standardized and clinically meaningful outcomes are needed before routine clinical implementation can be supported.